Kinematics and dynamics of mechanical systems : implementation in MATLAB and SimMechanics /: implementation in MATLAB and SimMechanics. (2015) - (Mechanical engineer), Russell, Kevin; (Mechanical engineer), Shen, Qiong; Sodhi, R. S (Raj S.)
No abstract available